Static Balance in Prediabetic Subjects: Correlation Study Involving Glucose Indicators, Insulin Resistance and Postural Stability Indices - Wang, Zhishan; Chen, Yihang; Yang, Weijun; Xie, Yuanya; Li, Miaoyun; Liang, Jingran; Li, Xingyu; Gao, LingJing; Pan, Dehong; Wang, Xiaoling; Chen, Shujiao (International journal of general medicine, 2025)
To investigate the relationship between different glycemic parameters and static balance function in prediabetic patients. A total of 92 prediabetic patients who attended The Third Affiliated Hospital of Fujian University of Traditional Chinese Medicine from October 2023 to February 2024 were enrolled in this observational study. All patients underwent assessments of glucose parameters, insulin resistance, and static balance function parameters. Spearman rank correlation test was used to analyze the correlations between these indices. Among the 92 participants, age, gender, height, weight, BMI, FIns, 2hPG, HOMA-IR, and HbA1c were correlated with static balance function. Specifically, age was negatively correlated with visual and vestibular function; height and weight were negatively correlated with proprioception; and BMI was negatively correlated with proprioception, vision, and vestibular function. 2hPG and HbA1c were negatively correlated with vestibular function and proprioception, respectively, while HOMA-IR and FIns were negatively correlated with vestibular function and vision. For patients with poorly controlled 2hPG or HbA1c, emphasis is recommended on coronal plane postural control training; for those with poorly controlled HOMA-IR or FIns, priority should be given to sagittal plane postural control training. Through multi-indicator correlation analysis, this study preliminarily identifies the potential mechanisms underlying the association between abnormal glucose metabolism and static balance dysfunction in prediabetic patients. These findings provide a reference for further exploration of clinical research on combined "glycemic control-balance training" interventions.